2013
DOI: 10.1063/1.4795844
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field induced ferroelectric transition of quasi one-dimensional frustrated quantum spin chain system Rb2Cu2Mo3O12

Abstract: Magnetic and dielectric properties have been studied for quasi one-dimensional spin 1/2 systems which are formed of edge-sharing CuO 4 square planes called CuO 2 ribbon chains. Due to the geometrical characteristic of the crystal structure of these systems, the nearest-neighbor exchange interaction J 1 between spins is relatively weak and often ferromagnetic, and the second neighbor interaction J 2 is antiferromagnetic. Under these situations, the helical ordering is often realized. Actually, LiVCuO 4 with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
5
29
1
Order By: Relevance
“…(ii) The other is an even-parity dimer state realized with large enough easyplane magnetic anisotropy. Furthermore, recent experiments have shown that the applied magnetic field in a range of 0.1-2.0 T induces a ferroelectric polarization in the absence of a magnetic spiral LRO without closing the spin gap 29 , possibly realizing the genuine spingapped vector-spin-chirality ordered state. Such vectorchiral ordered state can be realized under a weak Zeeman field 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The other is an even-parity dimer state realized with large enough easyplane magnetic anisotropy. Furthermore, recent experiments have shown that the applied magnetic field in a range of 0.1-2.0 T induces a ferroelectric polarization in the absence of a magnetic spiral LRO without closing the spin gap 29 , possibly realizing the genuine spingapped vector-spin-chirality ordered state. Such vectorchiral ordered state can be realized under a weak Zeeman field 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of these models is that a bulk electric polarization may emerge when interacting spins display a long-range ordered arrangement that breaks spatial inversion symmetry. Recently, the highly frustrated quantum spin system Rb 2 Cu 2 Mo 3 O 12 (RCMO) has been reported to display magnetic-field tunable ferroelectricity below ∼8 K, yet remarkably there is no evidence from bulk measurements for a concomitant transition denoting the onset of magnetic longrange order [11]. The system thus poses an enticing question: In the seeming absence of long-range magnetism, what is the physical origin of the magnetically tunable ferroelectricity?…”
Section: Introductionmentioning
confidence: 99%
“…1(a), the system has a monoclinic crystal structure with S = 1/2 Cu 2+ ions forming a quasi-one-dimensional ribbon chain network along the crystal b axis. Up to now single-crystal samples have not been successfully synthesized, and experimental studies of this system are performed on powder samples [11][12][13][14][15]. Early temperature * jonathan.white@psi.ch (T )-dependent magnetic susceptibility data evidenced RCMO to host strongly frustrated magnetic interactions that could be modelled according to a dominant nearest-neighbor ferromagnetic (FM) and next-nearest-neighbor antiferromagnetic (AFM) exchange interactions with a ratio J FM /J AFM ∼ −2.7 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ferroelectricity associated with the vector spin chirality order may appear robustly in the vectorchiral Haldane dimer phase without the long-range spiral magnetism, if the spin gap is enhanced [23] so that it dominates over the interchain interactions. Indeed, Rb 2 Cu 2 Mo 3 O 12 provides a unique example of a fieldinduced ferroelectricity hosted by a nonmagnetic ground state with a spin gap [16,17]. In this Letter, we report arXiv:1803.07081v1 [cond-mat.str-el] 19 Mar 2018 combined experimental and theoretical evidence that in the quasi-1D cuprate Rb 2 Cu 2 Mo 3 O 12 , a Haldane-gap ground state formed by emergent spin-1 pairs of S = 1/2 Cu spins ( Fig.…”
mentioning
confidence: 99%
“…with the g-factor g = 2. 16 [26] and the applied magnetic field B, where S σ, stands for an S = 1/2 spin at the site in the chain of edge-shared CuO 6 octahedra ( Fig. 1(e)) labeled by the index σ = ±.…”
mentioning
confidence: 99%